Next-Generation Sequencing Reveals Novel Homozygous Missense Variant c.934T > C in POLR1C Gene Causing Leukodystrophy and Hypomyelinating Disease - Naseer, Muhammad Imran; Abdulkareem, Angham Abdulrahman; Pushparaj, Peter Natesan; Saharti, Samah; Muthaffar, Osama Y. (Frontiers in Pediatrics, 2022)
Leukodystrophies are a diverse group of genetically established disorders categorized by unusual white matter changes in brain imaging. Hypomyelinating leukodystrophies (HLDs) include in a group of neurodevelopmental disorders that affect development of the myelin sheath in the brain. These disorders are categorized by developmental delay, spasticity, hypotonia along with intellectual disability. We described a patient with developmental delay, cerebellar ataxia, spasticity, hypotonia and having intellectual disability from a healthy family. Whole exome sequencing (WES) was performed to identify causative variant, which was further analyzed by bioinformatics analysts. WES was done and Sanger sequencing based segregation analysis confirmed the presence of the homozygous missense variants of NM_203290.3 c.934T>C p.Ser312Pro of RNA Polymerase I and III Subunit C (POLR1C) gene in this patient and heterozygous variant in unaffected carrier father and mother, supporting the pathogenicity and inheritance pattern of this variant. Further, the variant identified by WES was validated in healthy controls from population (n = 100) using Sanger sequencing analysis. Finally, our study explained the important use of WES in the disease diagnosis and provide further evidence that the variant in POLR1C gene may lead an important role for the development of hypomyelinating leukodystrophy in Saudi family.